Pengembangan LKPD Berorientasi Assessment for Learning untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik pada Materi Titrasi Asam Basa - Novita Indah Ramadhani; Muchlis (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2023)
AFL-oriented LKPD Development Research aims to determine feasibility LKPD terms of aspects validity, practicality, effectiveness to improve critical thinking skills in Acid-Base Titrations. This study uses research design Borg and Gall. Instrument validity includes an assessment/validation sheet. The practicality LKPD is seen from activity observation sheet and response questionnaire. The effectiveness LKPD is seen from the test critical thinking skills. The results showed that Assesment for Learning Oriented LKPD on acid-base titration material declared feasible. Judging from validation results, mode score of 5 is obtained which very valid in terms of content and construct validity. LKPD meets practicality criteria supported by results student activities are relevant to learning at meetings 1 and 2, namely 90% and 96%. Supported by positive response with percentage of 83% -100% with very good criteria. LKPD fulfilling effectiveness criteria in terms of students' critical thinking skills experience an increase in students' n-gain in the medium and high categories of 100%.